The war for oil - Strahan, David; BBC worldwide (Australia : BBC Worldwide, 2004)
Global oil production is in decline, and this may impact on the world economy by 2010. The Money Programme talks to the oil industry about the already raging battle to divide up the oil in a post-Saddam world, and goes on to ask whether a long-term solution to the oil crisis exists
Title from title screen
DVD format
Keywords: Petroleum industry and trade; Iraq War, 2003-